Intestinal Host-Microbe Interactions under Physiological and Pathological Conditions - Rodrigo Bibiloni; Eduardo J. Schiffrin (Hindawi Limited, 2010)
The intestinal mucosa is unique in that it can be tolerant to the resident, symbiotic microbiota but remaining, at the same time, responsive to and able to fight pathogens. The close interaction between host-symbiotic microbiota at the mucosal level poses important challenges since microbial breaches through the gut barrier can result in the breakdown of gut homeostasis. In this paper, hosts-integrated components that help to preserve intestinal homeostasis including barrier and immune function are discussed. In addition global alterations of the microbiota that can play a role in the initiation of an exaggerated inflammatory response through an abnormal signaling of the innate and adaptive immune response are briefly described.